2021
DOI: 10.1007/s00439-021-02271-6
|View full text |Cite
|
Sign up to set email alerts
|

A knockout mutation associated with juvenile paroxysmal dyskinesia in Markiesje dogs indicates SOD1 pleiotropy

Abstract: A juvenile form of paroxysmal dyskinesia segregated in the Markiesje dog breed. Affected pups exhibited clinical signs of a severe tetraparesis, dystonia, cramping and falling over when trying to walk. In most cases, the presentation deteriorated within weeks and elective euthanasia was performed. Pedigree analysis indicated autosomal recessive inheritance. Genome-wide association and homozygosity mapping of 5 affected dogs from 3 litters identified the associated locus on chromosome 31 in the region of SOD1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“… 25 In addition to this new human case, a truncating homozygous loss-of-function mutation in SOD1 was recently identified in Markiesje dogs that exhibited progressive tetraparesis and muscle wasting, in addition to brainstem and spinal cord atrophy. 63 However, it is notable that Sod1 knockout mice do not replicate the severe motor neuron phenotype that develops in humans despite developing a significant, motor neuropathy in later life in addition to visceral symptoms such as liver tumours, sarcopenia, and ocular symptoms. 56 , 64–66 Given the relatively young age of the patients described here, later-onset conditions associated with a loss of SOD1 function cannot be ruled out at this stage.…”
Section: Discussionmentioning
confidence: 99%
“… 25 In addition to this new human case, a truncating homozygous loss-of-function mutation in SOD1 was recently identified in Markiesje dogs that exhibited progressive tetraparesis and muscle wasting, in addition to brainstem and spinal cord atrophy. 63 However, it is notable that Sod1 knockout mice do not replicate the severe motor neuron phenotype that develops in humans despite developing a significant, motor neuropathy in later life in addition to visceral symptoms such as liver tumours, sarcopenia, and ocular symptoms. 56 , 64–66 Given the relatively young age of the patients described here, later-onset conditions associated with a loss of SOD1 function cannot be ruled out at this stage.…”
Section: Discussionmentioning
confidence: 99%
“…Propofol-induced dystonic movements have been reported anecdotally in dogs (so-called "propofol shakes"). The nature of these shakes T A B L E 2 Additional publications (not included in the consensus report on canine dyskinesia 1 ) related to canine and feline dyskinesia and synopsis of the presented findings [15][16][17][18]71 Publication Synopsis (epileptiform or not) is unknown. A single case report describes propofol-induced dystonia in a Golden Retriever.…”
Section: Drug-induced Dystoniamentioning
confidence: 99%
“…Examples include the reported positive effect of anti-seizure medications and muscle-relaxing drugs such as diazepam on the severity and duration of PxD in dogs. 1,[15][16][17][18] Another example is treatment of spastic paresis in cattle by partial tibial neurectomy. The recent consensus report on dyskinesias in dogs discusses neuroanatomic structures involved in the control of movement and posture, in particular the basal nuclei (e.g., caudate nucleus, putamen) and cerebellum.…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Two point mutations in SOD1 are known to cause degenerative myelopathy in a variety of dog breeds (Zeng et al 2014) and are animal models for amyotrophic lateral sclerosis in humans. In this issue, Mandigers et al (2021) identified a frameshift mutation in the Dutch Markiesje dog breed that leads to an autosomal recessive form of juvenile paroxysmal dyskinesia. This research provides an animal model for a juvenile, progressive spastic tetraplegia, and axial hypotonia (OMIM 618598).…”
Section: Novel Findings Identified For Inherited Diseases In Dogsmentioning
confidence: 99%